Practical guide for clinical neurophysiologic testing : EP, LTM, IOM, PSG, and NCV - Yamada, Tōru, 1940- (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"This book provides advanced content that begins where the "Practical Guide for Clinical Neurophysiologic Testing: EEG" ends. This advanced guide, more geared to neurology fellows than to electroneurodiagnostic technologists, discusses evoked potentials, including visual, brainstem auditory, and somatosensory EPs. The author covers intraoperative neurophysiologic monitoring, epilepsy monitoring, long-term bedside EEG monitoring, and sleep studies"--Provided by publisher.